CUFFLESS BLOOD PRESSURE DEVICES AND INCONSISTENT TRACKING OF BLOOD PRESSURE CHANGES. (April 2021) - Tan, Isabella; Barin, Edward; Gueguen, Cindy; Head, Geoff; Avolio, Alberto; Butlin, Mark
Abstract : Objective: Single point calibration is common in cuffless blood pressure (BP) measurement devices. Consequently, they may be apt at re-assessing BP at that same calibration BP but have potential for increased error as BP changes from that calibration point. This study investigates one pulse waveform-based (BPro, HealthStats) and one pulse arrival time-based (Maisense Freescanâ) cuffless device in their tracking of BP changes as compared to that of conventional cuff-based oscillometric devices. Design and method: 14 participants had 24-hour assessment of BP using BPro and a validated cuff-based oscillometric device (BPLab, Petr Telegin). Nocturnal BP dipping as measured by both devices was compared. In a separate study, six participants had BP measured with a validated cuff-based oscillometric device (OMRONâ HEM-7121) and either the BPro (n = 3) or Freescanâ device (n = 3) before and during a 2-minute cold-pressor challenge. BP change from baseline as reported by the devices were compared. Results: Average nocturnal fall in BP (mean ± SD) as reported by the cuff-based device and BPro were -15 ± 8% and -10 ± 6% (p = 0.061), respectively, for systolic BP; -19 ± 8% and -10 ± 7% (p = 0.008), respectively, for diastolic BP. Nocturnal dipping (defined as nocturnal fall > 10% in either systolic or diastolic BP) was detected in 6 participants with the BPro device as opposed to 14 as detected with the cuff-based device. During cold-pressor challenge, Freescanâ reported a systolic BP change of -4 ± 8 mmHg compared to the cuff measured change of 12 ± 8 mmHg (p = 0.017). BPro followed a similar trend to the Freescanâ device and reported a systolic BP change of -2 ± 2 mmHg compared to the cuff measured change of 14 ± 4 mmHg (p = 0.002). Conclusions: The BPro device was able to track nocturnal dipping in some but not all participants, with significant underestimation of nocturnal dipping in diastolic BP. Cold-pressor challenge induced BP changes that were unable to be detected by the cuffless devices. Whilst single point calibration may permit a cuffless device to assess when BP returns to that calibration point, tracking of BP changes appears to be inconsistent. Further investigation is required to understand the underlying factors that contribute to this inconsistency.